Wings of fire. Book nine, Talons of power: the graphic novel - Sutherland, Tui, 1978-; Sutherland, Tui, 1978-; Deutsch, Barry; Swirsky, Rachel (Sutherland, Tui, 1978- Wings of fire (Graphic novel), 2026)
"For every villain, there is a hero...Turtle the SeaWing isn't one of the heroes he reads about in stories. If he were, he'd use his animus powers to help Pyrrhia-- instead of keeping his abilities a secret. Now that Darkstalker, the charming but dangerous dragon from Pyrrhia's most notorious legends, has returned, Turtle knows what he needs to do: hide. And stay hidden. As he watches Darkstalker from the shadows, Turtle realizes that someone needs to stop the powerful dragon. A real hero. But Turtle is running out of time to find one, which means...he might have to save the day himself"--Jacket flap.